Knowledge and attitude of sex education among secondary school students in south-western Nigeria: A cross-sectional study - I.Y. Ademuyiwa; S.J. Ayamolowo; T.E. Oshinyemi; K.J. Oyeku (Elsevier, 2023)
Sex education helps in preparing adolescents to have responsible attitudes and behaviour towards sex for a harmonious sexual life. This study assessed the level of knowledge and attitude towards sex education among secondary school students in an urban south-western Nigeria.The study adopted a descriptive cross-sectional design. Multistage sampling technique was used to select a sample size of 378 students from a population of 3674 students in public secondary schools. A pre-tested self-administered questionnaire with Cronbach' Alpha value of 0.76 was used for data collection. The approval of the study was obtained from the Human Research Ethics Committee of Lagos University Teaching Hospital. Data were analyzed using SPSS version 20. Chi-square test and multiple logistic regression were used for test of association among the variables at p < 0.05.Majority of the respondents 338 (89.9%) were between age 14-17 with mean age of 16 ± 5.22 years. Majority of the respondents 309 (82.1%) had a good knowledge of sex education. More than half, 216 (57.5%) of the respondents had positive attitude towards sex education. There was a significant relationship between knowledge and attitude of the respondents towards sex education (p = 0.01). Knowledge of sex education increases as class of students increases to SS2 = (OR = 7.750; 95% CI [3.268-18.378] and SS3 = (OR = 2.219; 95% CI [1.067-4.613] respectively.The study concluded that the respondents had good knowledge of sex education and there was a significant relationship between students' knowledge and attitude towards sex education. There is need for awareness and effective sex education among secondary school students. Teachers and parents should create the view of improving the attitude of secondary school students towards sex education.